Developing A Teaching Factory Management Model to Improve Entrepreneurship Programs and Industry-Based Student Competencies in Vocational High School - Agustiani; Yari Dwikurniangsih (Postgraduate, University of Mataram, 2025)
Teaching Factory in Vocational High Schools (SMK) is a forum to facilitate SMK students to have competencies, with the hope that SMK graduates can be ready for entrepreneurship and have competencies that are in accordance with industrial needs. This study aims to develop a SMK Teaching Factory management model that aims to improve entrepreneurship programs and industry-based student competencies in SMK by implementing the POAC (Planning, Organizing, Actuating, Controlling) management function. The type of research conducted is the Borg and Gall Research and Development model modified into five stages, using a qualitative approach. Data were collected through questionnaires and interviews with Teaching Factory managers and validated using technical and source triangulation. The data analysis technique was carried out using qualitative descriptive analysis of the Miles and Huberman model. This research produces a management model, model description, and guidance for using the Teaching Factory model for Vocational High Schools. The results of a limited initial field trial conducted by the Teaching Factory manager indicate that the Teaching Factory management model can be implemented in Vocational High Schools with a score of 89.33% in the good category. This finding explains that the application of the POAC management function in the Teaching Factory management model can facilitate Vocational High School students to improve entrepreneurship programs and industry-based competencies.